Aripiprazole Lauroxil, a Novel Injectable Long-Acting Antipsychotic Treatment for Adults with Schizophrenia: A Comprehensive Review - Kunal Maini; Haley Gould; Jessica Hicks; Fatima Iqbal; James Patterson; Amber N. Edinoff; Elyse M. Cornett; Adam M. Kaye; Omar Viswanath; Ivan Urits; Alan D. Kaye (MDPI AG, 2021)
Purpose of Review. This is a comprehensive review of the literature regarding the use of Aripiprazole lauroxil for schizophrenia. This review presents the background, evidence, and indications for using aripiprazole lauroxil to treat schizophrenia in the context of current theories on the development of schizophrenia. Recent Findings. Schizophrenia is a chronic mental health disorder that currently affects approximately 3.3 million people in the United States. Its symptoms, which must be present for more than six months, are comprised of disorganized behavior and speech, a diminished capacity to comprehend reality, hearing voices unheard by others, seeing things unseen by others, delusions, decreased social commitment, and decreased motivation. The majority of these symptoms can be managed with antipsychotic medication. Aripiprazole lauroxil is a long-acting intramuscular injection that works as a combination of partial agonist activity at D2 and 5-HT1A receptors combined with antagonist activity at 5-HT2A receptors. It can be dosed as a 4-, 6-, or 8-week injection, depending on oral dosage. Aripiprazole lauroxil was FDA approved in October of 2015. Summary. Schizophrenia is a severe psychiatric disorder if left untreated. There are multiple medications to help treat schizophrenia. One antipsychotic agent, aripiprazole lauroxil, offers long duration injections that optimize and improve compliance. Known side effects include weight gain, akathisia, neuroleptic malignant syndrome, tardive dyskinesia, and orthostatic hypotension. Aripiprazole lauroxil is an FDA-approved drug that can be administered monthly, every six weeks, or every two months and has been shown to be both safe and effective.